Investigating SSH Research and Publication Practices in Disciplinary and Institutional Contexts. A Survey-Based Comparative Approach in Two Universities - Bayer, Florian; Gorraiz, Juan; Gumpenberger, Christian; Itúrbide, Arantxa; Iribarren-Maestro, Isabel; Reding, Steve (Frontiers in Research Metrics and Analytics, 2019)
In this paper, we comparatively analyze, present and discuss the results from a survey on increasing the visibility of research achievements in the social sciences and humanities (SSH) that was carried out at the University of Vienna (Austria) and the University of Navarra (Spain) in 2016 and 2017. Covering four major topics—searching and finding literature, publishing, the visibility of research, and the assessment of research outputs—we ask the following questions: are there disciplinary differences to be identified, and how do they present themselves in the two institutional contexts? Discussing the results, we showcase how disciplinary and institutional traditions and contexts are important factors that influence research and publication practices in the SSH. Our results indicate that the practices of searching and finding literature as well as publication practices and behavior are shaped by disciplinary traditions and epistemic cultures. On the contrary, assessment and valuation of research outputs are influenced by institutional and national contexts in which SSH research is organized and carried out.